The Role of Halal Living on Muslim Millennial in Applying Halal Lifestyle - Fitri Sarasati (Universitas Muhammadiyah Mataram, 2018)
Halal has currently become lifestyle and trend that spread out in the community. Realizing the new tendency, NetTV as one of the media industries in Indonesia presents a program called Halal Living. The program contains information about travel, halal culinary, fashion hijab, health and beauty closely related to the life of Muslim women. An impression is expected to spread a positive and acceptable message by the public. According to the Stimulus-Organism-Response (S-O-R) theory, humans will produce certain behaviors if there is a certain stimulus; thus, the effect is a reaction to the stimulus. Stimulus in this research is the message delivered in program; the organism an informant who is a Muslim millennial; while the response awareness of halal lifestyle. In this research, halal living impressions will be seen from knowledge, attitude, and motivation of the informant. Informant's knowledge concerns the informant’s understanding about the impressions and messages presented. Informant’s attitudes deal with likes or dislikes regarding the impressions and messages presented. Motivation of informant concerns the desire of informants to apply the message or information delivered throughout the program. This study aimed to analyze the role of halal living show on Muslim millennial in applying halal life. It used qualitative descriptive approach. The data were collected using observation and semi-structured interview with Muslim millennial born in 1980-1995. The results reveal that Muslim millennial are interested in watching halal living program because the values it contains is well-packaged; the host is the hijaber, who is an Indonesian Muslim influencer; and messages it delivers are applicable and effective.